Effect of Submucosal Mesna Application on Mucoperichondrial Elevation in Septoplasty - Dogan, REMZİ; EREN, SABRİ BAKİ; Yenigun, ALPER; YENİGÜN, ALPER; Eren, SABRİ BAKİ; TUĞRUL, SELAHATTİN; Ozturan, ORHAN; Goktas, Seda Sezen; DOĞAN, REMZI; Tugrul, Selahattin; ÇALIM, ÖMER FARUK; Calim, Omer Faruk; et al. (My University, 2017)
Objective: It was revealed that the thiol compound named mesna chemically softens the connective tissue with submucosal injection, and facilitates the endoscopic submucosal dissection. The authors aimed to investigate the effect of mesna injection on mucoperichondrial elevation during septoplasty operation. Methods: This study was planned as a patient-control study and performed. Fifty-six patients who had septoplasty operation were divided into 2 groups that are submucosal mesna (group 1) and submucosal saline (group 2) applied ones. In both groups, the measurement was initiated by a timer during the start of septal incision and elevation processes. After bilateral subperichondrial and subperiostal elevation were finished, timer was stopped and time was recorded. After that, mucosal integrity was reviewed and mucosal damage status was recorded. The difficulty of mucoperichondrial elevation for the surgeon was recorded for each patient. Results: Twenty-five (44.7%) of the patients who participated in our study were females while 31 (55.3%) were males. The average elevation periods were 201.4 +/- 74.3 seconds in group 1 and 260.2 +/- 84.1 seconds in group 2. In mesna applied patients, elevation period was statistically and significantly shorter (P = 0.009). Impairment in mucosal integrity was observed as 33.3% in group 1 and 58.8% in group 2. In mesna applied patients, significantly less impairment in mucosal integrity was observed (P = 0.031). The average mucoperichondrial elevation difficulty for the surgeon is observed as 4.83 +/- 2.47 in group 1 and 6.5 +/- 1.9 in group 2. Mesna applied patients were defined as significantly easier patients for the surgeon (P = 0.006). Conclusion: Submucosal mesna application is an approach that provides a convenient, fast, and effective mucoperichondrial elevation in septoplasty and protects the mucosal integrity.